In the Eyes of the Beholder: Border enforcement, suspect travellers and trafficking victims - Ham, Julie (Anti-trafficking review, 2013)
Over the past decade, the border and border policing has figured as central to identifying and responding to trafficking. This article draws on original research into immigration officers’ decision-making — both at the border and within the nation — to identify the persistent preoccupation with suspect travellers. Examining research in Australia and Thailand that spans seven years, the article brings together research that demonstrates the predominance of the binary category of victim of trafficking/unlawful migrant worker and highlights the ambiguity of daily decision-making processes that categorise women who come into contact with immigration authorities. While the policy rhetoric is based on categories and risk profiles for identifying suspected victims of trafficking or those deemed at risk, we contribute to the growing body of work that has highlighted the presence of gendered and racialised stereotypes in immigration decision-making and consider implications this may have on women’s mobility across and within borders